Brazilian Modernization and Urban Planning In TheNineteenth Century - Schmidt, Benicío (Urban History Review / Revue d'histoire urbaine, 1980)
The state has played a decisive role in the modernization cum urbanization of Brazil since 1850. Three examples of state intervention are described in some detail: the state guarantees of the paulista railway network, which integrated several regional economic complexes; the foundation of the regional capital, Belo Horizonte, which allowed a leading faction of the elite to expand its control; the building and organization of Brasilia, whereby the state redirected internal migration and regional occupation.